2013
DOI: 10.1002/ajhb.22455
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal variability in the pelvis and limb skeleton of humans: Does stabilizing selection limit female pelvic variation?

Abstract: The results suggest that stabilizing selection does not limit variability in the female pelvic canal. Biological plasticity may be greater in the canal than that in other skeletal regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 45 publications
6
63
0
1
Order By: Relevance
“…Accordingly, we hypothesized that correlational selection has produced patterns of covariance between pelvis shape and other body dimensions. Earlier studies based on smaller sets of linear measurements could not clearly demonstrate such patterns (37)(38)(39)(40).…”
Section: Fig 2 Sexual Dimorphism In the Human Pelvis (A)mentioning
confidence: 79%
“…Accordingly, we hypothesized that correlational selection has produced patterns of covariance between pelvis shape and other body dimensions. Earlier studies based on smaller sets of linear measurements could not clearly demonstrate such patterns (37)(38)(39)(40).…”
Section: Fig 2 Sexual Dimorphism In the Human Pelvis (A)mentioning
confidence: 79%
“…In relation to the obstetric dilemma, he suggested that such constraints may have reduced the overall evolvability of the birth canal in earlier hominins, but that these constraints became weaker in later hominins. A study of regional skeletal variability in recent human populations found that the pelvic canal was, in fact, the most variable trait, suggesting that stabilizing selection is no longer a major constraint [36].…”
Section: Resolution Of the Dilemma By Genetic Adaptationmentioning
confidence: 99%
“…A human infant's head enters the inlet facing laterally, and then rotates, usually to face backwards, as it exits through the more anteroposteriorly oriented outlet (figure 2). Although the precise orientation of the infant may vary depending on variations in the shape of the maternal birth canal, this rotation during birth is consistent among humans [4]. In contrast with an ape baby, who passes through the outlet posteriorly between the ischial tuberosities, a human baby emerges more anteriorly, under the ischiopubic rami, owing to the inferior position of the sacrum [33,35].…”
Section: Pelvic Morphology In Humans and Nonhuman Primatesmentioning
confidence: 99%
“…Each of these processes is essential enough to survival and reproductive success as to be under strong pressure from natural selection [1][2][3][4]. As a result, the fossil record of the evolution of the human pelvis over the past 4.5 Myr reveals a profound story concerning selective priorities during different phases of human evolution, and elucidates the essential constraints that formed our modern anatomical condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation